Optimizing Amphibious Reconnaissance Effectiveness through the Use of Unmanned Aerial Vehicles (UAVs) in Marine Operations - Soemarto, Huda Prawira; Komaruddin, Komaruddin; Yani, Ahmad (AGUSPATI Research Institute, 2025)
This studyi aims to analyze the rolei of Unmanned Aerial Vehicles in supporting the tasks of Amphibious Reconnaissance Soldiers in carrying out Amphibious Operation Tasks and to determine the effectiveness of Unmanned Aerial Vehicles in determining the position of Amphibious Reconnaissance Soldiers who are carrying out amphibious operation tasks. Policies, strategies and efforts are also carried out to support amphibious operation tasks. The approaches employed in this research are qualitative and descriptive methods. The information gathered has been collected, processed, and descriptively analyzed utilizing the SWOTi analysis tool, a qualitative method conducted by assessing both internal and external factors. The resultsi of this studyi indicatei that the role iof Unmanned Aerial Vehicles in supporting the tasks of Amphibious Reconnaissance Soldiers in carrying out Amphibious Operation Tasks internally, the greatest strength lies in the protection and accuracy provided by UAV support (the highest score values in strength: 0.97 and 0.52). While from the external side, the greatest opportunities come from the effectiveness and cooperation factors (scores 0.6 and 0.8). In carrying out amphibious operation tasks, it is inseparable from technical and environmental threats, such as extreme weather disturbances, weak GPS signals, or electromagnetic interference from the enemy. Strategies that can be implemented to optimize the use of Unmanned Aerial Vehicles in supporting Marine Amphibious Reconnaissance soldiers for the success of amphibious operations by increasing the integration of UAVs with the command and control system of the Amphibious Reconnaissance unit. Based on the main strengths in the form of protection (score 0.97) and accuracy (0.52). Policies in the form of strengthening doctrine, defense equipment, increasing personnel capabilities and continuous training. While the strategy used is the use of UAVs as long-distance reconnaissance tools, monitoring the operational field, and synergy tools with other dimensions. The efforts made are to conduct special education, UAV maintenance, development of modern military technology and increase cybersecurity